2020
DOI: 10.1038/s41563-020-0684-x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical cell stiffness is independent of substrate mechanics

Abstract: Cortical stiffness is an important cellular property that changes during migration, adhesion, and growth. Previous atomic force microscopy (AFM) indentation measurements of cells cultured on deformable substrates suggested that cells adapt their stiffness to that of their surroundings. Here we show that the force applied by AFM onto cells results in a significant deformation of the underlying substrate if it is softer than the cells. This 'soft substrate effect' leads to an underestimation of a cell's elastic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 49 publications
8
81
0
Order By: Relevance
“…Also, the nature of the material under test as well as the technical limitations and conditions of the testing equipment and the environment itself do influence the results and need to be accounted for with precision and reported thoroughly. For instance, in a recent paper it was shown that the Hertz model per se is not correct for the measurements of cells on very soft substrates, calling for a more elaborate model [30]. On a more technical point, the methods for calibration and determination of the contact point in the curves (position when the tip first contacts the material under test) are absolutely critical [31].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the nature of the material under test as well as the technical limitations and conditions of the testing equipment and the environment itself do influence the results and need to be accounted for with precision and reported thoroughly. For instance, in a recent paper it was shown that the Hertz model per se is not correct for the measurements of cells on very soft substrates, calling for a more elaborate model [30]. On a more technical point, the methods for calibration and determination of the contact point in the curves (position when the tip first contacts the material under test) are absolutely critical [31].…”
Section: Introductionmentioning
confidence: 99%
“…As a confounding factor, it has been proposed that the culture substrate could affect the measurement results of cell elasticity and viscosity when indenting to depths which are larger than 5% of the sample thickness [40]. Nevertheless, concurrent with the recently proposed guidelines to eliminate a possible substrate effect [41], we measured microglial cell thickness and corrected our measurements according to the mean cell thickness. In addition, cell measurements where the probe extended into the cell at a depth > 10% of cell thickness were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The Young's modulus (E) was determined from the force-distance curves. The force-distance curves were analyzed using the "Composite Cell-Substrate" (CoCS) model for adherent cells over soft substrates (50) and a custom pipeline written in MATLAB. The 1024 pixels acquired for each quantitative image map were split into categories "background" or "cell" by thresholding the histogram of the pixel height values using Otsu's method.…”
Section: Cell Mechanics Analysismentioning
confidence: 99%